Knowledge and attitudes of patients with nephrolithiasis: a crosssectional study - Miranda da Silva, Gabriela; de Aguiar Ristow, João Victor; do Nascimento Lima, Helbert (O Mundo da Saúde, 2022)
Nephrolithiasis is a common urinary tract disease with an increasing prevalence, mainly due to the lack of control of modifiable risk factors. The aim of this study was to assess the level of knowledge about risk factors for nephrolithiasis and patients' attitudes. This is a cross-sectional, observational, descriptive, and analytical study based on a review of medical records and through an online survey of patients diagnosed with nephrolithiasis during follow-up at a private nephrology clinic in Joinville, Brazil. Gender, age, comorbidities, laboratory values, knowledge, and attitudes were evaluated. An explanatory multivariate model was proposed to assess the effect of knowledge and attitudes on risk factors for nephrolithiasis. Of the 129 participants, 44 (34%) were men, median age 42 years and median time to diagnosis 5 years. Hypertension was the most prevalent comorbidity in 26%. In 42% of patients, there was weight gain since the first consultation. Alone, excessive salt consumption (98%), low water intake (77%) and high protein consumption (67%) were the most identified risk factors. After adjusting for confounders, greater knowledge was not associated with weight gain (OR=0.94; 95% CI 0.73-1.22; p=0.661) or lower salt intake (OR=1.26; 95% CI 0.95-1.67; p=0.106). Greater knowledge was associated with greater daily fluid intake (OR=1.50; 95% CI 1.11-2.01; p=0.008). Although there is little knowledge of all nephrolithiasis risk factors, measures to increase awareness can contribute to preventive attitudes.